Dampak Belanja Subsidi dan Bantuan Sosial dari APBD terhadap Kesenjangan Pendapatan di Indonesia - Sandi Asep Ramdani (Direktorat Sistem Perbendaharaan, 2024)
Creating equitable development is one of the Government's policy priorities. This research analyzes the influence of subsidy spending and social assistance from the APBD on income inequality as measured using the Gini coefficient with control variables, namely capital expenditure and education (average years of schooling). Panel data regression with Ordinary Least Square (OLS) with Robust Standard Error and Difference in Differences (DiD) was used to analyze data from 34 Provinces in Indonesia in the 2007-2022 period. The results of data analysis using OLS show that spending on subsidies, social assistance and capital has a positive effect on the Gini coefficient, while education has a negative effect on the Gini coefficient. Meanwhile, DiD's analysis shows that provinces with higher actual spending on subsidies and social assistance than the national average have higher income gaps in the 2015-2022 period. Based on these findings, there are indications that the distribution of subsidies and social assistance is still not on target. The Government needs to improve the subsidy spending scheme, improve data on social assistance recipients, and strengthen monitoring and supervision in its distribution.